Through ruminant nutrition to human health: role of fatty acids. (19th October 2016) - Savoini, G.; Farina, G.; Dell'Orto, V.; Cattaneo, D.
Abstract : In the last decades, a new awareness on human nutrition has increased and the concept of 'food' has changed from 'source of nutrients for body's needs' to 'health promoter'. Fruits and vegetables have always been considered beneficial for human health. More recent studies have demonstrated that bioactive components are also present in animal-derived foods, such as milk and dairy products. A broader concept of 'nutritional safety' implies the knowledge of how the nutrients contained in animal-derived foods positively affect human health, and how to increase their content. The improvement of dairy products fatty acid (FA) composition can involve strategies in animal nutrition. This review aims to discuss the role of FAs supplementation in ameliorating milk fat composition, environmental impact and animal health. In particular, we have focused on the role of n-3 and CLA FAs and how animal nutrition strategies can positively affect both human and animal health. Several studies have demonstrated that through adequate nutritional strategies is possible to manipulate and improve FA composition of milk and derived products (cheese). Moreover, feeding animals with n-3 FAs has proved to reduce emission of methane (CH4 ), but further nutritional strategies are needed in order to address this crucial environmental issue. In relation to animal health, n-3 FAs have been proved to modulate immune and inflammatory response in dairy ruminants. Recent studies have addressed the potential programming effects of increased maternal n-3 polyunsaturated FAs intake on offspring's immune functions showing that feeding bioactive FAs to pregnant animals can affect progeny health status.